SS 316L/HA composite via powder injection moulding: Mechanical and physical properties - Johari, N. A.; F. R. M., Romlay; W. S., Wan Harun (Penerbit UMP, 2019)
The bio-active and biological affinity with bony tissue effect of hydroxyapatite (HA) marks as a chosen material for implants application. Uniting HA which has low mechanical properties that limit its application with a higher mechanical property of metallic biomaterial 316L stainless steel (316L) to form a biocomposite have been a solution to produce acceptable mechanical properties for human implant. The 316L/HA biocomposite would have attribute vital to current implant materials, like a low Young’s modulus, high compatibility, and bio-inertness. This study concentrates on investigating the mechanical and physical properties of the 316L/HA biocomposite fabricated by metal injection moulding. The synthesis HA was produced from calcium-Phosphate. While, Polypropylene (PP), Stearin Acid (SA) and primary binder, Paraffin wax (PW) used as a binder system. Different weight of HA (0, 5, 10 and 15 wt. %) ratios to SS 316L/HA were prepared. All samples were sintered at 1350 ºC for 2 hours soaking time. The result shows that 10 wt.% HA biocomposite and above have higher porosity and low mechanical strength. However, 5 wt.% HA biocomposite has a high relative density which 87.95% compared to other additive HA % and hardness 127.10 Hv. The Tensile strength and elongation of 316L/HA biocomposite exhibit decreased as the content of HA wt.% increase which similar properties with the human bone that lower than 130 MPa (tensile strength). Therefore, 5 wt.% HA biocomposite is found to be the most excellent powder ratio for 316L/HA biocomposite regarding mechanical and physical properties and to achieve the mechanical strength of the biocomposite is necessary an amount of HA content in the composite are smaller than 15 wt.%.